2015
DOI: 10.1002/pssa.201532488
|View full text |Cite
|
Sign up to set email alerts
|

Beam matching: A method to study phonon transport through interfaces and multilayer structures

Abstract: Structuring materials is one mechanism to influence the thermal conductivity and thus thermoelectric efficiency. In order to investigate the scattering of phonons in multilayer structures we developed a beam matching technique, which is based on the concept of individual phonons and their scattering at interfaces. One of the major goals is to efficiently determine the complex band structure of the bulk materials. The complex band structure is determined using selected k‐points on a triangulated grid in the com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…It has also been shown that TMM can be used to simulate second harmonic generation from multilayered structures and the optical response of switches[33b] and sensors . Investigation of phonon propagation in the multilayers even allows to determine thermal conductivity in multilayered structures …”
Section: Basic Optics Of Dbrsmentioning
confidence: 99%
“…It has also been shown that TMM can be used to simulate second harmonic generation from multilayered structures and the optical response of switches[33b] and sensors . Investigation of phonon propagation in the multilayers even allows to determine thermal conductivity in multilayered structures …”
Section: Basic Optics Of Dbrsmentioning
confidence: 99%